2010
DOI: 10.1021/jo100022t
|View full text |Cite
|
Sign up to set email alerts
|

Carbenes with Reduced Heteroatom Stabilization: A Computational Approach

Abstract: High-level DFT calculations, coupled with appropriate isodesmic reactions, are employed to investigate the effects of monoheteroatom substitution, cyclization, and unsaturation on the stability, multiplicity, and reactivity of amino-, oxy-, silyl-, phosphino-, and thioalkylcarbenes. The results of these calculations are compared to those of di-tert-butylcarbene, 2,2,5,5-tetramethylcyclopentanylidene, and 2,2,5,5-tetramethylcyclopent-3-enylidene as the reference molecules. The calculated singlet-triplet energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 79 publications
0
29
1
Order By: Relevance
“…20 Remarkably, despite the widespread use of azolium ion precursors to NHCs in organocatalysis and elsewhere, there have been relatively few literature reports of the solution kinetic or thermodynamic Brønsted acidities of these precatalysts, [21][22][23][24][25][26][27][28][29][30][31][32] although there have been studies of NHC nucleophilicities 33 and gas phase proton affinities. [34][35][36][37][38][39][40][41][42] Washabaugh and Jencks reported on the C2-H/D exchange and aqueous pK a values of a range of N-alkyl thiazolium ion analogues of thiamine, that are precursors to thiazol-2-ylidenes 1. [27][28][29] Amyes et al reported aqueous pK a values for the conjugate acids of N,N-dialkylimidazol-2-ylidenes 2 (R = R' = H or Me) and two benzoannelated variants.…”
mentioning
confidence: 99%
“…20 Remarkably, despite the widespread use of azolium ion precursors to NHCs in organocatalysis and elsewhere, there have been relatively few literature reports of the solution kinetic or thermodynamic Brønsted acidities of these precatalysts, [21][22][23][24][25][26][27][28][29][30][31][32] although there have been studies of NHC nucleophilicities 33 and gas phase proton affinities. [34][35][36][37][38][39][40][41][42] Washabaugh and Jencks reported on the C2-H/D exchange and aqueous pK a values of a range of N-alkyl thiazolium ion analogues of thiamine, that are precursors to thiazol-2-ylidenes 1. [27][28][29] Amyes et al reported aqueous pK a values for the conjugate acids of N,N-dialkylimidazol-2-ylidenes 2 (R = R' = H or Me) and two benzoannelated variants.…”
mentioning
confidence: 99%
“…Considering the wide variety of heteroatom substituted carbenes, it seems necessary to thoroughly probe the effects of heteroatom substitution, cyclization, and unsaturation on the stability of parent form of dialkylcarbenes leading to information on the structures, characteristics and behaviors of these species. Hence, following our interest in the novel stable singlet carbenes,45, 46 the parent acyclic diethylcarbene is selected to probe the effect of π‐donor/σ‐acceptor (NH and O), π‐donor/σ‐donor (PH and S), and π‐acceptor/σ‐donor substitution (SiH 2 ) on the singlet–triplet energy gap (Δ E S–T ) (Fig. 1).…”
Section: Introductionmentioning
confidence: 93%
“…This can be attributed to n/p interactions of the heteroatoms with the vacant p-orbital of the silylene center which competes exclusively with the interaction of the occupied Walsh orbital (W/p). Due to the conjugation of heteroatom lone pairs with the double bond in unsaturated cyclic silylenes 3 Y , the cyclopropyl plays a more important role in singlet state stabilization [41]. For example the singlet state of 3 N is stabilized by cyclopropyl twice the singlet state of 2 N (11.0 vs. 5.8 kcal mol À1 , Table 4).…”
Section: Tablementioning
confidence: 99%
“…Increasing DE SeT of dimethylcarbene upon simultaneous cyclization and unsaturation [41,42], made us probe such effects on our silylenes (3 Y , Fig. 1).…”
Section: Introductionmentioning
confidence: 99%